Pelatihan Pembuatan Kompos Berbasis Limbah Penyulingan Terna Nilam di Kecamatan Teunom Aceh Jaya - Chairuddin Chairuddin; Muhammad Afrillah; Amda Resdiar; Nana Ariska; Sumeinika Fitria Lizmah; Dewi Junita; Evi Julianita Harahap (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service aims to increase the knowledge and skills of the patchouli farming community in Teunom District in making compost based on patchouli distillation waste. The method of implementing this service used training, which included the stages of counseling, demonstrations, mentoring, and evaluation. Participants participating in this activity were patchouli farmers, totaling 15 people. The evaluation instrument for this activity used a questionnaire and was analyzed descriptively. This dedication showed (1) an increased participant's understanding of compost, and (2) an increased participant's skills in making patchouli waste-based compost.